Service centres in rural India : policy, theory and practice - Wanmali, Sudhir (Delhi, 1983)
The study is placed within the growing field of interest in government policy and its impact on service provision in rural areas of India. The study is critical of the current urban, and industries, based models of rural development. It notes that such models have sometimes succeeded, but most of the times failed, because the requisite mechanisms for spatial deve lopment were missing from, but were assumed to exist in, such models. The study has demonstrated that it is not necessary to base the programmes for the development of rural areas exclusi vely on urban, and industrial, centres and that it is possible to view rural development as an entirely rural process involving agriculture, service provision and agro-based industries. The facts that a dynamic situation has been analysed (spread over a period of ten years (1968-1978), in structurally two different areas (irrigated and the dry tracts) and involving locations and spread of rural (government sector controlled) and retail (private and traditional sector controlled) services make the study more interesting. Although based on field surveys in rural India, the findings of the study have a wider relevance.
Keywords: Rural development India